The relationship between audit components and audit expectation gap in listed companies on the Tehran stock exchange. Issue 1 (17th January 2020) - Salehi, Mahdi; Jahanbin, Fariba; Adibian, Mohammad Sadegh
Abstract : Purpose: The expectation gap between auditors and users has recently been the topic of many controversies. This paper aims to evaluate the relationship between auditor's characteristics and audit expectation gap among information users in listed companies on the Tehran stock exchange market. In other words, the study attempts to find whether there is a significant relationship between audit components and the audit expectation gap or not. Design/methodology/approach: The multiple regression model is used to test the hypotheses. Research hypotheses are tested using a sample of 78 listed companies on the Tehran stock exchange during 2012-2016, by using integrated data technique of the multiple regression model. Findings: The findings show that standard audit fees are not significantly associated with the audit expectation gap. Furthermore, audit fees are negatively associated with the audit expectation gap, which provides that allocated audit price in financial statements gives useful information for external and internal individuals. Predictably, it is recommended that audit opinion significantly determines the level of the audit expectation gap. The authors also find that the independence of the director boards and audit committee members fulfill the expectation gap of individual users. Moreover, finding the negative impact of audit firms ranking on the expectation gap, supports the idea of higher ranked audit firms provide high quality services, and consequently, more reliable information. Finally, the results show that the audit record is positively associated with the audit expectation gap. Originality/value: As all recent studies on the expectation gap were qualitative, the present study is the first paper, which measures the expectation gap quantitatively through the statistical method.